Gracilaria sp. in Asajaya mangrove with special reference to its production - Siti Masila, Maslie (Universiti Malaysia Sarawak, UNIMAS, 2010)
This study aimed to record the biomass and identifies the species of Gracilaria that inhabit the Asajaya mangrove area. The Asajaya mangrove has been divided into three stations and Station 3 was further divided into five permanent plots. The samples of Gracilaria sp. were collected monthly from September to December 2009 at the five permanent plots. Taking the tree of Sonneratia alba as a centre, Gracilaria was collected around the tree with radius of 10 m from the centre. The samples were dried in oven for 48 hours at 60°C and weighed to obtain the dry weight. Gracilaria changii is the species that has been identified in this study. The temperature in Asajaya mangrove ranged from 27°C to 30.2°C. The pH was recorded as alkaline which ranged from 7.54 to 7.66. For salinity, it ranged from 20.3 PSU to 21.9 PSU. Meanwhile dissolved oxygen (DO) ranged from 6.7 mg/L to 9.7 mg/l. The biological oxygen demand in 5 days (BOD5) recorded the lowest value in Station 1 with 7.08 mg/l and the highest in Station 2 with 10.63 mg/l. Biomass (g dry weight/m2) was calculated for each subplot and its ranged from 0.04 to 0.21 g/m2 DW. The agar yield without alkali treatment is 15 ± 0.77% and 17 ± 0.85% for alkali treatment.